Oral Leukoplakia: An Overview of Histopathological Spectrum Focusing On WHO Grading System and Binary System of Oral Epithelial Dysplasia: Oral Leukoplakia: Histopathological Spectrum Focusing On Oral Epithelial Dysplasia - Naushin, Tehmina; Iqbal, Zafar; Khan, Abbas Saleem; Mehmood, Uzma; Khan, Tanweer; Mahmood, Sidra; Hassan, Mahmood Ul; Mahmood, Momina; Hassan, Tayyab Ul (Pakistan Journal of Health Sciences, 2025)
Oral leukoplakia by definition is a white patch with uncertain risk, not including other lesions that could develop into cancer. Objectives: To assess the histopathological spectrum of oral leukoplakia and focus on their relation with WHO-classified histological grades and binary system of dysplasia. Methods: This study comprised patients diagnosed with oral leukoplakia. Hematoxylin and eosin-stained slides of 60 cases were assessed based on the World Health Organization 2005 classification system: epithelial precursor lesions and binary system of oral epithelial dysplasia. The chi-square test was used to compare different categorical variables related to oral leukoplakia. For analyzing data SPSS version 20.0 was used. Results: Of the 60 oral leukoplakia subjects 43 (71.7%) were found to be male while 17 (28.3%) were female. Whereas 26 cases showed dysplastic features (n=26, 43.3%) Among the cases of oral epithelial dysplasia, a higher number of cases of moderate dysplasia was observed (n=12, 46.1%) followed by severe dysplasia (n=10, 38.5%), and the least number of cases had mild dysplasia (n=4, 15.4%). There was a statistically significant relationship between the binary system of oral epithelial dysplasia and variants of oral epithelial dysplasia, mildly dysplastic, moderately dysplastic, and severely dysplastic epithelium (p<0.04). Conclusions: It was concluded that as oral leukoplakia is such a disorder having a high chance of conversion into cancer early detection is of utmost importance to prevent conversion into malignancy. In addition to the WHO Classification of the said lesions, a binary system of dysplasia can also be promoted.